(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study investigated the strategies of teaching English as a Second Language in multilingual classrooms at Lower Grades in primary schools in Meheba Refugee Settlement in Kalumbila District of Zambia. The objectives were to establish the strategies employed in teaching of English as a second language in multilingual classrooms; analyze how the strategies are used and investigate materials used with the strategies. To address these objectives, a phenomenological qualitative descriptive design was employed. The study was guided by Vygotsky’s Social Learning Theory. Data were collected through interview guide and lesson observation protocol; on a sample of 18 teachers drawn from five selected primary schools. Narrative analysis was employed. The findings indicated that translation, code switching, look and say, group work, class discussions, question and answer, body language and phonemic awareness were the strategies teachers employed in the teaching of English as a Second Language in multilingual classrooms. The study further found that the strategies were used in the teaching of different components of English Language such as vocabulary, prepositions, dialogue and comprehension in the multilingual classrooms. The data also revealed that Chalkboard, English Readers (Textbooks) and Flash cards were the most commonly used teaching and learning materials in the multilingual classrooms that were studied. The findings revealed there was over reliance on the use of chalkboard and question and answer in the lessons. The study concludes that variety of strategies and teaching and learning materials are employed in teaching English as a Second Language in multilingual classrooms. The study recommends that teaching English as a Second Language in multilingual classrooms should involve the use of different strategies that enhance learning among learners. Teachers should think out of the box when deciding on what teaching and learning materials to use besides depending on the usual common chalkboard, textbooks and flash cards.